The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-02141-1
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate classification techniques and mass spectrometry as a tool in the screening of patients with fibromyalgia

Abstract: Fibromyalgia is a rheumatological disorder that causes chronic pain and other symptomatic conditions such as depression and anxiety. Despite its relevance, the disease still presents a complex diagnosis where the doctor needs to have a correct clinical interpretation of the symptoms. In this context, it is valid to study tools that assist in the screening of this disease, using chemical work techniques such as mass spectroscopy. In this study, an analytical method is proposed to detect individuals with fibromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…This m/z ratio value was indicated in the analysis of PC1 loadings, being present in most data sets. Another reason that highlights this finding is in a previous study 18 which also confirms the presence of compounds of the lysophosphatidylcholine class in the samples of the cases group, as well as in studies that present this class of metabolites as a possible biomarker or contributing factor to the fibromyalgia phenotype 31 , 32 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This m/z ratio value was indicated in the analysis of PC1 loadings, being present in most data sets. Another reason that highlights this finding is in a previous study 18 which also confirms the presence of compounds of the lysophosphatidylcholine class in the samples of the cases group, as well as in studies that present this class of metabolites as a possible biomarker or contributing factor to the fibromyalgia phenotype 31 , 32 .…”
Section: Discussionsupporting
confidence: 74%
“…Despite proposing some adjustments in the use of the criteria, the study concluded that the criteria had good sensitivity and specificity for all analyzed studies, with an average of 84% and 83%, respectively 8 . Recent studies have also demonstrated good sensitivity and specificity in classifying groups of patients with and without fibromyalgia, using blood plasma samples, among which: Passos et al 17 used ATR-FTIR spectroscopy, with results of 89.5% sensitivity and 79% specificity in the classification between controls and fibromyalgia patients using a GA-LDA model; while Alves et al 18 used PSI-MS mass spectrometry and reached values of 100% sensitivity and specificity using SPA-LDA and exploratory analyzes with PCA, with small groups of samples (10 controls and 10 fibromyalgia samples). The study presented herein obtained 100% sensitivity and 75% specificity (88% accuracy), with a total number of samples equal to 64 (27 controls and 37 fibromyalgia samples) for the classification performed with the PCA-LDA model in the set of data regarding the moderate CAT symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Features (NFF) questionnaire may be a valuable primary screening tool (7). • Studies underlined high salivary cortisol levels, alterations in metabolites involved in free radical, lipid and amino acid metabolism and in blood cytokine profiles (13)(14)(15)(16)). • Neuro-inflammation has been highlighted by OCT and [11C]-(R)-PK11195 PET (18,19).…”
Section: • the Nociplastic-based Fibromyalgiamentioning
confidence: 99%
“…[ 65 ] reported that PCA does more feature classification, while LDA does more data separation which is in accordance with our results. Likewise, previously reported data by Alves et al [ 66 ] applied nine different algorithms to find the best identification tool for fibromyalgia. They inferred that SPA-LDA is a reliable tool in the clinical diagnosis of fibromyalgia.…”
Section: Discussionmentioning
confidence: 98%